Plan de exportación para el producto té de moringa hacia el mercado de Madrid – España - Tumbaco Calderón, Giselle Carolina (2018)
Ecuador is an exporting country by nature, its main products have been well seen by international traders who manage to make agreements so that these national goods can be consumed in other markets, taking advantage of this pattern, the idea of creating a tea export plan was raised moringa ice cream, this plant that is currently generating high expectations in the environment for its health benefits. The production company MorinVital S.A. was taken into consideration, which according to he study maintains a problem: the sales at the local level do not compensate the projections that are why the idea previously mentioned as the proposal was chosen…..